Muscle cell derived angiopoietin-1 contributes to both myogenesis and angiogenesis in the ischemic environment - McClung, Joseph M.; Reinardy, Jessica L.; Mueller, Sarah B.; McCord, Timothy J.; Kontos, Christopher D.; Brown, David A.; Hussain, Sabah N. A.; Schmidt, Cameron A.; Ryan, Terence E.; Green, Tom D. (Frontiers in Physiology, 2015)
Recent strategies to treat peripheral arterial disease (PAD) have focused on stem cell based therapies, which are believed to result in local secretion of vascular growth factors. Little is known, however, about the role of ischemic endogenous cells in this context. We hypothesized that ischemic muscle cells (MC) are capable of secreting growth factors that act as potent effectors of the local cellular regenerative environment. Both muscle and endothelial cells (ECs) were subjected to experimental ischemia, and conditioned medium (CM) from each was collected and analyzed to assess myogenic and/or angiogenic potential. In muscle progenitors, mRNA expression of VEGF and its cognate receptors (Nrp1, Flt, Flk) was present and decreased during myotube formation in vitro, and EC CM or VEGF increased myoblast proliferation. Angiopoietin-1 (Ang-1), Tie1, and Tie2 mRNA increased during MC differentiation in vitro. Exogenous Ang-1 enhanced myogenic (MyoD and Myogenin) mRNA in differentiating myoblasts and increased myosin heavy chain protein. Myotube formation was enhanced by MC CM and inhibited by EC CM. Ang-1 protein was present in CM from MCs isolated from both the genetically ischemia-susceptible BALB/c and ischemia-resistant C57BL/6 mouse strains, and chimeric Tie2 receptor trapping in situ ablated Ang-1’s myogenic effects in vitro. Ang-1 or MC CM enhanced myotube formation in a mixed isolate of muscle progenitors as well as a myoblast co-culture with pluripotent mesenchymal cells (10T1/2) and this effect was abrogated by viral expression of the extracellular domain of Tie2 (AdsTie2). Furthermore, mesh/tube formation by HUVECs was enhanced by Ang-1 or MC CM and abrogated by Tie2 chimeric receptor trapping. Our results demonstrate the ability of muscle and endothelial cell-derived vascular growth factors, particularly Ang-1, to serve as multi-functional stimuli regulating crosstalk between blood vessels and muscle cells during regeneration from ischemic myopathy.